Intervensi Metode Drill Melalui Pre Dan Post Conference Terhadap Kemampuan Perawat Menerapkan Terapi Reminiscence - Ni Made Diah Natalia Indrasari; Ni Made Nopita Wati; Ni Luh Putu Thrisna Dewi; Made Nursari (Lembaga Penelitian dan Pengabdian Masyarakat (Stikes Panrita Husada Bulukumba), 2020)
Reminiscence therapy is a type of cognitive therapy, which uses memory to maintain mental health and improve the quality of life of the elderly. Nurses are expected to be able to provide reminiscence therapy according to Standard Operating Procedures. The drilling method is a learning method to form a habit so that it can increase the ability of nurses to provide reminiscence therapy. The purpose of this study was to determine the effect of the drill method through pre and post-conference on the ability of nurses to apply reminiscence therapy. This type of pre-experimental research, using a One-group pre-post test design. The number of samples is 10 people with purposive sampling. Data collection using the observation sheet. The results showed that the average pre-test nurse's ability was 70.769, including in the sufficient category, increasing to 95.899 when the post-test was in a good category. The results of the Paired t-test statistical test showed that the value of p = 0.000 <0.05 and count = 7.503> t table df 9 = 2.262. This shows that there is an effect of the drill method through pre and post-conference on the ability of nurses to apply reminiscence therapy. The drilling method can improve nurses' ability to apply SOP, especially reminiscence therapy through regular exercises with frequent frequency and sequentially according to the steps in SOP.